POLA REKRUTMEN CALON LEGISLATIF DAERAH PADA PEMILU LEGISLATIF 2014 ( STUDI PERBANDINGAN DPD PKS DENGAN DPC DEMOKRAT KABUPATEN INDRAGIRI HULU ) - Reza Fahlevi Utomo; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Three times elections are held democratically, ie in 1999, 2004 and 2009 has become a place of natural selection for political parties. Large and powerful party will remain alive while the small and the weak will be eliminated by itself. Proven in the 2004 elections, of which there are dozens of political parties, only a few political parties that managed to fulfill his ambition to win the battle power struggle. Namely Golkar, PDI-P, PKB, PPP, PAN, PKS and the Democratic Party is a political party of seven who succeeded in dominating the political landscape in the national legislature. In this case, there is an important task that must be carried out by political parties in general are recruiting legislative candidates. Point to define the candidates in the legislature either national or regional. Recruitment legislators is very important to be done by any political party if the democratization process in Indonesia is really aimed at creating social welfare for all the people of Indonesia. Because one of the functions of political parties is as a means of political recruitment, search and talent for getting people active in politics as a member of the party, as well as select members of the party are gifted to be prepared to be good candidates for leader of the party leaders, members of the representative body of the people as well as the head of The purpose of this study was to determine the mechanism of recruitment of candidates DPD and DPC PKS Democratic Party and to know what criteria are used by the DPD and DPC PKS Democrats in determining Indragiri Hulu legislative candidates in legislative elections in 2014 state public officials and / or governments, regional head also elected by the people. The theory used in this study is the theory of political recruitment, one of which according to Ramlan Surbakti, that includes election political recruitment, selection, and appointment of a person or group of people to carry out a number of roles in the political system in general and government in particular. The method used in this study is qualitative.In the present study found a variety of things about the recruitment patterns both in the MCC and in DPC DPD Democrat Indragiri Hulu. Both parties are equally open recruitment in determining candidates. But there are different mechanisms between the two because each party has its own procedures in conducting recruitment candidates. In PKS party, recruitment is done through the sequence; committee formation PUI (General Internal Committee), stage PUI (socializing, networking, verification of candidates, elections and voting), then the new set by DPW through candidates decree and registered to the ElectionCommission. In the Democratic party, formed BAPPILU Agency (winning elections), then BAPPILU do; file selection candidates, the selection of candidates, and the final determination and registered to the Election Commission. One of the differences between them, ie if the MCC is to establish the legislative branch of the Provincial candidates decree, while Democrats are selected directly and immediately determined by DPC District not to the level Province. Similarities between the MCC and the mechanism can be seen from the Democrat candidates openly reception mechanisms, both internal and external. So it can be concluded that the pattern of recruitment between the MCC and the Democratic candidate is different, even though both carry an open mechanism. It happens because each party has its own rules in the recruitment of candidates.Keywords : Patterns, Recruitment, Mechanisms, Legislative.